Evidence of Interdomain Ammonium Cross-Feeding From Methylamine- and Glycine Betaine-Degrading Rhodobacteraceae to Diatoms as a Widespread Interaction in the Marine Phycosphere - Zecher, Karsten; Hayes, Kristiane Rebecca; Philipp, Bodo (Frontiers in Microbiology, 2020)
Dissolved organic nitrogen (DON) compounds such methylamines (MAs) or glycine betaine (GBT) occur at detectable concentrations in marine habitats and are also produced and released by microalgae. For many marine bacteria, these DON compounds can serve as carbon, energy and nitrogen source, while microalgae can usually not use them. Previously, it had been shown that Donghicola sp. strain KarMa -a member of the marine Rhodobacteraceae- can cross-feed ammonium from monomethylamine (MMA) degradation to the diatom Phaeodactylum tricornutum leading to the establishment of a mutual metabolic interaction under photoautotrophic conditions. In the present study it was investigated whether this interaction has a broader impact on bacteria-diatom interactions in general. Cross-feeding between strain KarMa and P. tricornutum was possible with di- and trimethylamine as well as with GBT. Cross-feeding of strain KarMa could also be observed in co-cultures with the diatoms Amphora coffeaeformis and Thalassiosira pseudonana with MMA as sole nitrogen source. Based on the in silico analysis of MA and GBT degradation pathways, algae-associated Rhodobacteraceae type strains were postulated to interact with P. tricornutum in a similar manner as strain KarMa. Ammonium cross-feeding of these type strains (such as Celeribacter halophilus, Roseobacter denitrificans, Roseovarius indicus, Ruegeria pomeroyi, Sulfitobacter noctilucicola) after methylamine degradation showed species-specific patterns, whereas bacterial GBT degradation led always to diatom growth. In conclusion, degradation of DON compounds by members of the Rhodobacteraceae family and the subsequent cross-feeding of ammonium may represent a widespread, organism-specific and regulated metabolic interaction for establishing and stabilizing the association with photoautotrophic diatoms in the oceans.